Multi-path transmission strategy and congestion control scheme for multimedia sensor networks - SHA Chao1; SUN Li-juan1; WANG Ru-chuan1; HUANG Hai-ping1 (Tongxin xuebao)
A multi-path transmission method for multimedia sensor networks was proposed.By considering the transmission time,residual energy as well as transmission rate of the wireless links,three classes of paths are established with the help of metadata packets.Network congestion rate is reduced as well by adjusting time intervals of sampling.Experiments results show that this method is well performed on packet loss,real-time transmission as well as congestion control.